Improving the efficiency and stability of inorganic red perovskite light-emitting diodes using traces of zinc ions. Issue 46 (16th November 2021) - Cai, Xiao-Yi; Yu, Yi; Ye, Yong-Chun; Shen, Yang; Guo, Ming-Lei; Wang, Jing-Kun; Shen, Kong-Chao; Li, Yan-Qing; Tang, Jian-Xin
Abstract : Enhanced efficiency and operational stability are achieved for all-inorganic red perovskite light-emitting diodes using traces of zinc ions for defect passivation, leading to a prolonged half-lifetime up to 2667 hours. Abstract : Metal halide perovskite light-emitting diodes (PeLEDs) have been recognized as emerging candidates for next-generation solution-processed electronic display technology, and great progress has been made in recent years. However, their poor operational stability is yet to be solved. Here, we present a reformative all-inorganic red-emission PeLED based on the passivation effect caused by the incorporation of zinc ions into perovskites for enhancing the efficiency and operational stability. A high-quality quasi-two-dimensional perovskite CsPbI3− x Br x thin film with good crystallinity is obtained, benefiting from the combination of large organic ammonium ions (PEA + ions) and inorganic salt zinc iodide (ZnI2 ). As a result, ZnI2 -passivated CsPbI3− x Br x PeLEDs emitting at 666 nm show a maximum external quantum efficiency of 9.93% and a maximum brightness of 4258 cd m −2 . More importantly, the PeLEDs achieve a long half-lifetime of about 2667 h at an initial luminance of 100 cd m −2 . This work provides a facile method to obtain stable and efficient red-emission PeLEDs.